2013
DOI: 10.1177/1708538112473978
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of mean platelet volume in thromboangiitis obliterans

Abstract: Thromboangiitis obliterans (TAO) affects small- and medium-sized vessels of the extremities via a non-atherosclerotic inflammatory process in the elderly. Although diagnostic criteria have been determined, only a few studies have been described in the laboratory features. Diagnostic biomarkers are important for reducing disruptions caused by TAO. The diagnostic importance of mean platelet volume (MPV) was investigated in TAO patients. Forty-four patients diagnosed with TAO (study group) and 45 healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…21 On the other hand, some of the complete blood counting parameters reactivity are also shown in atherosclerotic events such as high platelet reactivity is associated with increases in both atherosclerosis burden and plaque calcification in previous reports. 12,22 In the view of these correlations, our results supported that increased bone marrow reactivity may play a role in progression of disease. According to our results, high plasma RDW and MPV levels can be sourced by increased bone marrow reactivity and this process should be investigated with further clinical researches.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…21 On the other hand, some of the complete blood counting parameters reactivity are also shown in atherosclerotic events such as high platelet reactivity is associated with increases in both atherosclerosis burden and plaque calcification in previous reports. 12,22 In the view of these correlations, our results supported that increased bone marrow reactivity may play a role in progression of disease. According to our results, high plasma RDW and MPV levels can be sourced by increased bone marrow reactivity and this process should be investigated with further clinical researches.…”
Section: Discussionsupporting
confidence: 79%
“…MPV has been suggested to be a guide to identify high-risk patients with disturbed microcirculation related disease in previous reports. 15 In another study reported by Yavuz et al., 12 the authors argued that higher MPV levels might be a predictor of disrupted peripheral circulation. The results of this study correlates similarly with to our study, diverging with PAD population being thromboangiitis obliterans patients.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Increased MPV has been reported to correlate with intracoronary thrombus burden in the IRA before mechanical reperfusion, in-hospital major adverse cardiovascular events in patients with STEMI undergoing PCI [7,8], and 1-year incidence of death or myocardial infarction in patients with acute coronary syndrome undergoing PCI [9]. Furthermore, recent studies by Demirtas et al [10] and Yavuz et al [11] showed there is an interaction between MPV and disease severity in many types of arterial-occlusive diseases, such as peripheral artery disease and thromboangiitis obliterans. However, the association between MPV and myocardial reperfusion in patients with STEMI and successful epicardial reperfusion after PCI has not been fully investigated.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, it has been emphasized that these parameters may be predictive in vascular diseases. While MPV values are predicted to have a diagnostic predictive value in patients with thromboangiitis obliterans involving the distal vascular bed, which is a disease very similar to RP, on the other hand, NLR values were also found to be associated with intima-media thickness in patients with Behcet's disease [ 9 , 10 ]. In addition, monocyte chemoattractant protein-1 (MCP-1) is a serum inflammation parameter that has been investigated in similar conditions and it has been less studied in vascular system diseases compared to other parameters [ 11 ].…”
Section: Introductionmentioning
confidence: 99%